Rice husk substrates and pruning time for gypsophila production - Höhn, Daniela; Peil, Roberta Marins Nogueira; Perin, Lais; Marchi, Priscila Monalisa; Grolli, Paulo Roberto; Wieth, Albertina Radtke (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
This research evaluated the growth, yield and quality of gypsophila New Amore® variety grown in gutters filled with substrate in a system with leaching recirculation in southern Brazil. The treatments were the result of the combination of four substrates [carbonized rice husk (CRH100%), raw rice husk (RRH100%), CRH + organic commercial substrate S10 (Beifort®) (15%) and RRH+S10 (15%)] with two pruning times (early and late). The substrates did not affect the dry matter partitioning between the flowers and vegetative organs or the balance between the shoot and root growth. However, RRH100% reduced the shoot growth, flower stem yield and quality. The CRH100% and RRH+S10 substrates can be indicated for gypsophila cultivation once, in a general way, they presented promising results. The late pruning increased the gypsophila growth and yield and benefited the quality of the stems. The gypsophila plants adapted well to the employed crop system.